Erich Fromm and the Critical Theory of Communication. Issue 3 (August 2020) - Fuchs, Christian
Erich Fromm (1900–1980) was a Marxist psychoanalyst, philosopher, and socialist humanist. This article asks: How can Fromm's critical theory of communication be used and updated to provide a critical perspective in the age of digital and communicative capitalism? In order to provide an answer, this article discusses elements from Fromm's work that allow us to better understand the human communication process. The focus is on communication (the second section), ideology (the third section), and technology (the fourth section). Fromm's approach can inform a critical theory of communication in multiple respects: His notion of the social character allows to underpin such a theory with foundations from critical psychology. Fromm's distinction between the authoritarian and the humanistic character can be used for discerning among authoritarian and humanistic communication. Fromm's work can also inform ideology critique: the ideology of having shapes life, thought, language, and social action in capitalism. In capitalism, technology (including computing) is fetishized and the logic of quantification shapes social relations. Fromm's quest for humanist technology and participatory computing can inform contemporary debates about digital capitalism and its alternatives.